The status of fish in Malaysian diets and potential barriers to increasing consumption of farmed species - Goh, Ee Von (2018)
The thesis took an interdisciplinary, problem-oriented approach to address the research problem: ’Is farmed fish capable of replacing wild-caught fish in the Malaysian diet?’ The main objectives of the project were to assess current fish consumption habits, evaluate the impacts of these on sustainability of fish stocks and determine whether aquacultured products could be a suitable substitution. A combination of data collection methods was used, namely dietary assessments, systematic literature review, market research interviews and surveys and analysis of electronic and paper-based official records. The review of the Malaysian food balance sheets showed a significant transition in diet over the last three decades, specifically with respect to an increase in animal protein by approximately 60% over this time, with fish as the major source of protein. To further explore the contribution of fish to the diet of Malaysians, and any ethnic and geographical differences in consumption, a food frequency questionnaire (FFQ) was developed to assess habitual dietary intakes within selected coastal, rural and urban populations across different cultural groups in Klang Valley. The FFQ provided a clearer picture of the quantities of fish consumed by Malaysians and enabled the characterisation of Malaysian fish consumers based on the types of fish species consumed for sustainability assessment purpose. The nutritional contribution of wild versus farmed fish was compared and contrasted. Results from this study, combined with detailed studies of perception of wild versus farmed fish by consumers, aquaculturists and wholesalers, provided a greater understanding of the factors that influence consumers’ fish buying and consumption habits. The key findings are discussed with respect to the sustainability of the current situation, potential for expanding the aquaculture sector to replace wild fish in the Malaysian diet and recommendations for future research and issues for policy makers involved in the expansion of the industry.